Effect of repeatedly heated palm olein on blood pressure regulating enzymes activity and lipid peroxidation in rats - Leong, X.F.; Salimon, J.; Mustafa, Mohd Rais; Jaarin, K. (Penerbit Universiti Sains Malaysia, 2012)
Background: Oxidative stress is associated with the pathogenesis of cardiovascular diseases. Deep-fat frying process of dietary cooking oil plays a role in the generation of free radicals. Palm olein heated to 180°C temperature was tested for its effect on the activity of blood pressure regulating enzymes and lipid peroxidation. Methods: Forty-two adult male Sprague-Dawley rats were equally assigned into six groups. First group was fed with normal rat chow as control group, and the subsequent groups were fed with rat chow fortified with 15% weight/weight of fresh palm olein, palm olein heated once, palm olein heated twice, palm olein heated five times or palm olein heated ten times, respectively. Feeding duration was six months. Fatty acid analyses of oil were performed using gas chromatography while peroxide values were determined using standard titration method. Plasma was collected for biochemical analyses. Results: Repeatedly heated palm olein increased peroxide value, angiotensinconverting enzyme level, lipid peroxidation, and reduced heme oxygenase level. Fresh palm olein and palm olein heated once had lower lipid peroxidation and better outcome in blood pressure regulating enzymes activity than repeatedly heated palm olein. Conclusion: Repeatedly heated palm olein may deteriorate the activity of blood pressure regulating enzymes and increase lipid peroxidation.